Experimental Study of the Probability Distributions on the Seakeeping Performance of Monohull and Catamaran Design - Ali, Baharuddin; Firdaus, Nurman (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
A safety and a comfort criteria of ship, one of them which can be known from ability of the ship motion on sea wave. The development of maritime technology in particular shipbuilding, catamaran ship design is one of the considerations in modern ship design, in addition to monohull ship design. This research describes the analysis of seakeeping model test of monohull and catamaran ship. The seakeeping model test is performed on sea- state 4 with a heading of 45 deg, 90 deg, 135 deg and 180 deg. Ship motion responses in the form of heave, pitch and roll motion, are presented in the form of the probability distribution curves. From the results of seakeeping test, it can be seen that the catamaran ship provides motion response relatively smaller than the monohull ship.